Impact of positron emission tomography with the use of fluorodeoxyglucose on response to induction chemotherapy in patients with oropharyngeal and hypopharyngeal squamous cell carcinoma. (May 2013) - Kawakita, Daisuke; Masui, Takashi; Hanai, Nobuhiro; Ozawa, Taijiro; Hirakawa, Hitoshi; Terada, Akihiro; Nishio, Masami; Hosoi, Hiroshi; Hasegawa, Yasuhisa
Abstract Conclusion: Maximum standardized uptake values (SUVmax) have prognostic value for induction chemotherapy (ICT) response and survival in oropharyngeal and hypopharyngeal squamous cell carcinoma (OHSCC) patients. Pretreatment positron emission tomography with the use of fluorodeoxyglucose (18F-FDG PET) may be an aid in deciding the treatment strategy in OHSCC patients. Objectives: We investigated the association between pretreatment 18F-FDG PET and response to ICT and survival in OHSCC patients. Methods: We conducted a retrospective cohort study of 58 OHSCC patients treated at Aichi Cancer Center Hospital. The predictive impact of SUVmax of the primary tumor site was evaluated using statistical multivariate proportional hazard models. Results: Thirty-one cases (53%) were located in the oropharynx and 27 (47%) in the hypopharynx. Median SUVmax was 11.6 (range 3.2–23.5), and was significantly higher in the 8 patients with less than stable disease than in the 50 with more than partial response (median SUVmax, 17.3 vs 11.1; p = 0.002). In multivariate analysis, hazard ratios for the medium and high SUVmax groups relative to the low group were 3.07 (95% confidence interval, 0.62–15.29; p = 0.170) and 4.71 (0.97–22.89; p = 0.055), respectively, and the dose-response relationship was statistically significant (ptrend = 0.047). A similar tendency was observed on subclassification by oropharynx and hypopharynx.